Post-traumatic events disorders and their relationship to psychosocial adjustment among female students of the Faculty of Physical Education and Sports Sciences - Dr. Amer Saeed; Dr. Aymen Hani; Dr. Saleema Abdullah (الرياضة المعاصرة)
Wars constitute a negative source for society as a whole, including students and others who suffer the impact and negative consequences of tensions and anxiety that may confuse and distract them while they perform their work. Hence the work of researchers in the College of Physical Education and Sports Sciences at the University of Babylon to reveal what female students may suffer from post-traumatic events, especially those who live in hot spots that have suffered from these ongoing battles and wars. In order to try to find out what psychological and social compatibility the female students may enjoy, the research aims to identify the following: